THE STUDENT'S ABILITY IN TRANSLATING TEXT: PROBLEM AND SOLUTION - Zulfikar Noor (Universitas Negeri Islam Sumatera Utara, 2023)
Translation, vocabulary, and grammar are just three of the many problems that are linked with the English language. The purpose of this study is to determine the challenges that students have when attempting to translate written information into English so that they can understand what is being said or written in English. And A descriptive research methodology was utilised for this investigation. This research was carried out with the participation of 25 different students, and the findings revealed that the students exhibited a good ability to translate content from Indonesian to English. The vast majority of students showed off their abilities to translate phrases from Indonesian to English. The sentences contain fundamental noun phrases that refer to the present, the past, and the future, as well as active and passive forms of the noun. Despite this, there were a few students who were still confused about how to switch between active and passive or passive and active. Keywords: Students' Translating Problem, Translation, Translating Text